A Pap test does not screen for everything: Nurse practitioner knowledge of ovarian cancer. Issue 3 (9th July 2014) - Loerzel, Victoria Wochna; Hunt, Debra; Rash, Elizabeth
Abstract Purpose Nurse practitioners (NPs) are in a prime position to educate women about initial signs and symptoms of ovarian cancer (OC) and perform appropriate screening tests. However, little is known about NPs knowledge regarding OC. This article's purpose is to present the outcomes of a focused OC awareness program for NP students. Data sources NP students (N = 104) participated in this longitudinal one group pre–post study. Knowledge was calculated based on the number of correct answers for a total knowledge score and subscales related to OC incidence, risk, screening, symptoms, and treatment. An item related to the effectiveness of the Pap test to screen for OC was evaluated separately. Conclusion Knowledge deficits continue to exist related to OC, emphasizing the need for NPs to be aware of risk factors, symptoms, and early detection options for women with average risk. Many NP students erroneously believed a Pap test was an effective screening tool for OC. Implications for practice Many NPs are inadequately prepared to assess risk, detect early symptoms, and perform screening tests for OC. Continuing education and reinforcement about OC is essential if NPs are to provide appropriate education to clients and detect this deadly disease as early as possible.